The sexual and reproductive health needs of school-going young people in the context of COVID-19 in rural KwaZulu-Natal, South Africa - Natsayi Chimbindi; Ursula Ngema; Nothando Ngwenya; Andrew Gibbs; Candice Groenewald; Guy Harling; Nondumiso Mthiyane; Busisiwe Nkosi; Janet Seeley; Maryam Shahmanesh (My University, 2022)
Background: The impact of school closures due to COVID-19 raised widespread concerns about children's health and well-being. We examine the impact on the sexual health needs of learners in the context of COVID-19 related lockdowns in rural KwaZulu-Natal, South Africa.Methods: In july-November 2020 and August-November 2021 we conducted 24 in-depth interviews and 8 group discussions with teachers and learners from 4 schools, community members and key education stakeholders. All interviews were conducted by telephone. We used a thematic analysis approach and Nvivo 12 software to manage the data.Results: Four main themes related to the COVID-19 pandemic emerged from the data: the sexual and reproductive health (SRH) of learners in the lead-up to the pandemic; the impact of COVID-19 on learners' SRH and wellbeing; the opportunities schools provided to support sexual well-being of learners during the pandemic; and the role of schools in supporting SRH for learners during the pandemic. Learners and stakeholders reported that the SRH of young people was affected by alcohol misuse, poor SRH knowledge and few pathways to link learners with services. Stakeholders working with schools reported that a lack of access to biomedical interventions (e.g., contraception) increased learner pregnancies. Gender-based violence in learners' households was reported to have increased during the COVID-19 pandemic related to loss of income. School closures disrupted the provision of a safe space to provide SRH and HIV-education through Life Orientation lessons and school nurse talks. This loss of a safe space also left learners vulnerable to sexual and physical violence. However, once schools re-opened, daily COVID-19 screening in schools provided the opportunity to identify and support vulnerable children who had other social needs (food and uniforms).Conclusion: The COVID-19 pandemic may have increased SRH needs and vulnerability of school-going children in a high HIV-burden rural setting. School shutdowns reduced the opportunity for schools to provide a vital safe space and information to enhance SRH for adolescents. Schools play a vital health promotion and social protection role.
Keywords: COVID-19; HIV; Life Orientation; adolescents; alcohol and substance abuse; pregnancy.